IDENTIFIKASI MOTIVASI DAN PENGEMBANGAN KUALITAS SUMBER DAYA MANUSIA SEBAGAI BENTUK UPAYA PENINGKATAN KINERJA PEGAWAI - Azzaroh, Lia Siti Fatimah (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Research aims to understand motivation and quality of human resources development to increase the employee performance.This study used a qualitative approach type use qualitative approach descriptive.Data collection procedures by means observation, interview, and documentation.The informants, using a technique 5r (relevance, recommendation, rapport, readiness, reassurance), objects on this study is the umkm home industry plisket drapery drapery and employees.The result of the research indicated that motivation given to the employee performance is the process well and employees receive some motivation to be applied in the workplace without any coercion because they need more spirit urge to work while quality of human resources development on the performance call employees by means, like own family dexterous, a rapid means work with maximum results. Novelty this research showed skill in work as a clerk plisket drapery must own employees , agile and also how quick but the results remain good.